KONTROVERSI PERATURAN PERUNDANGAN DALAM ACCRUAL ACCOUNTING - Kun Ismawati (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2016)
There are basic problems in the accrual accounting system application: some rules has supported the adoption of accrual accounting, but another still based on cash basis. The differences are in budgeting, income recognition, expenditure recognition, prepaid expenditure recognition, tax receivables recognition, unearned revenues recognition, and expenditure payable recognition. This paper examine the problems. The writer analyze that beside of the rules gaps, considerations of those differences are for controlling and efficiency purposes. The wri tersuggested the necessary adjusting the rules of accrual accounting in order to make everything goes well, and the most important thing is to prepare humanresources in facing the new system to get a good result.